(untitled) (Journal of the College of Education for Women, 2019)
I’ve dealt with marked (after the global economic crisis in the policy of the United States from 1929 to 1933) a set of facts and historical events that contributed to the shaping of American foreign policy during the economic crisis or Miaraf historic recession that hit the big capitalist world Thelatnaat the beginning of the last century, whereOur research included three main areas in which we tried to stabilize the political decision-making in the corridors of diplomacy, U.S. State Department has set off in this research study in three axes: the first included a knowledge of U.S. foreign policy with the countries of Central and South America in light of the global economic crisis 1929–1933. While the second axis included on an extrapolation of U.S. foreign policy with the countries of Europe in light of the global economic crisis. The third axis of the model takes a certain limit myself to my country, Japan and China on the continent, yellow and realities of U.S. foreign policy in particular has shown Tgahmha Japanese invasion of Manchuria, aregion of China. The study relied on a critical mass of resources, books, documentaries and foreign Arabic and translated to the number of messages and Alatarih university as well as the newspapers and scientific journals and periodicals was to benefit both of them within the historical period 1929 -1933 placed the search. The researcher reached at the end of his studies for the above set of results after examining the impact of the Great Depression on foreign policy skyrocket, as follow: • The global economic crisis has affected the policy of the United States of America State 1929 1933 directly, the general trend of Siirt, the State Department about international relations by virtue of discharge the global economic crisis left him with all aspects of life on the overall economic, social and political in the United States of America. • United States of America deliberately and seriously to settle their disputes by economic and political relations with countries of Central and South America, trying to win markets to overcome the economic crisis, which has achieved significant results in this light. . • as well as the economic crisis prompted the United States of America asking European countries to pay reparations and debts of the First World War because of the economic situation the U.S. confused.Where the United States during the years of economic crisis in urgent need of such compensation and debt, to address the mounting economic problem. • wanted the United States and through its involvement and presence of a number of international conferences and Alatagafaat weight and maintain the economic and political weight and become the undisputed mistress of the world. • represented the 1929-1933 global economic crisis has taken several dimensions aspects of political, economic and social influenced directly and arthralgia in the American political decisionmaking at the level of international relations.